Pragmatic randomised controlled trial of local corticosteroid injection and naproxen for treatment of lateral epicondylitis of elbow in primary care. Issue 7215 (9th October 1999) - Hay, Elaine M; Paterson, Susan M; Lewis, Martyn; Hosie, Gillian; Croft, Peter
Abstract: Objective: To compare the clinical effectiveness of local corticosteroid injection, standard non-steroidal anti-inflammatory drugs, and simple analgesics for the early treatment of lateral epicondylitis in primary care. Design: Multicentre pragmatic randomised controlled trial. Setting: 23 general practices in North Staffordshire and South Cheshire. Participants: 164 patients aged 18-70 years presenting with a new episode of lateral epicondylitis. Interventions: Local injection of 20 mg methylprednisolone plus lignocaine, naproxen 500 mg twice daily for two weeks, or placebo tablets. All participants received a standard advice sheet and co-codamol as required. Main outcome measures: Participants' global assessment of improvement (five point scale) at four weeks. Pain, function, and "main complaint" measured on 10 point Likert scales at 4 weeks, 6 months, and 12 months. Results: Over 2 years, 53 subjects were randomised to injection, 53 to naproxen, and 58 to placebo. Prognostic variables were similar between groups at baseline. At 4 weeks, 48 patients (92%) in the injection group were completely better or improved compared with 30 (57%) in the naproxen group (P<0.001) and 28 (50%) in the placebo group (P<0.001). At 12 months, 43 patients (84%) in the injection group had pain scores ≤3 compared with 45 (85%) in the naproxen group and 44 (82%) in the placebo group (P>0.05). Conclusions: Early local corticosteroid injection is effective for lateral epicondylitis. Outcome at one year was good in all groups, and effective early treatment does not seem to influence this.